Summary and conclusions [in Africa agriculture trade monitor 2023] - Odjo, Sunday P.; Traoré, Fousseini; Zaki, Chahir (AKADEMIYA2063, 2023)
Against the background of worldwide trade disruptions and climate change impacts, the 2023 Africa Agriculture Trade Monitor explores recent trends and patterns in Africa’s global and regional agricultural trade. Like the preceding editions, the report uses a database that corrects for discrepancies in trade flow values as reported by importing and exporting countries. This section summarizes the key findings discussed in the report’s six chapters and related policy implications for successful implementation of the African Continental Free Trade Area Agreement.